Strong Convergence Theorems for Solutions of Equations of Hammerstein Type - Chih-Sheng Chuang (Journal of Applied Mathematics)
We consider an auxiliary operator, defined in a real Hilbert space in terms of and , that is, monotone and Lipschitz mappings (resp., monotone and bounded mappings). We use an explicit iterative process that converges strongly to a solution of equation of Hammerstein type. Furthermore, our results improve related results in the literature.